2013
DOI: 10.4067/s0718-58392013000400005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vitamin E supplementation on growth performance, carcass characteristics and intramuscular fatty acid composition of Longissimus dorsi muscle in Tan sheep

Abstract: The beneficial effects on meat quality of adding vitamin E to diets have been extensively studied in cattle and lamb. However, how supplemental vit E affects the performance and meat quality of ʽTanʼ sheep has not been reported. Thirtyfive male lambs of ʽTanʼ sheep (20-30 d after weaning) with similar body weight were randomly divided into five groups of seven each to receive a basal diet plus five levels of vit E supplementation: 0 (control group, CG), 20, 100, 200, and 2000 IU d -1 lamb -1 . The results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 27 publications
3
11
0
Order By: Relevance
“…Furthermore, their report was also in contrast to the results of this study in terms of Vit C versus the control group. It also corroborated with a similar study where Vit E supplementation which had no influence on the growth performance of male 'Tan' Sheep lambs [21]. In agreement with this study, it was noted that Vit E supplementation had beneficial effect on performance of young animals [22].…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, their report was also in contrast to the results of this study in terms of Vit C versus the control group. It also corroborated with a similar study where Vit E supplementation which had no influence on the growth performance of male 'Tan' Sheep lambs [21]. In agreement with this study, it was noted that Vit E supplementation had beneficial effect on performance of young animals [22].…”
Section: Discussionsupporting
confidence: 91%
“…Maiorano et al () reported that lamb injected with a total dose of 1,350 mg vitamin E for a period of 15–64 days of age had lower slaughter weight, weight gain, and carcass weight compared with those of the control group. In another study, Zhao et al () found that lamb fed diet containing vitamin E supplementation at 100, 200, and 2000 IU/day over a feeding period of 130 days has lower average daily weight gain compared with control groups. This may be due to high intake of vitamin E in the diet which may suppress growth of the animals since the recommended minimal requirement for normal growth and health of sheep by the Agricultural Research Council (ARC, ) has been stipulated to be between 10 and 15 mg/kg dietary DM.…”
Section: Application and Roles Of Vitamin E In Livestockmentioning
confidence: 98%
“…Sheep which represent another type of small ruminant animal has received tremendous boost in terms of their performance as a result of vitamin E supplementation added to their diet. Recent reports have shown that dietary supplemental of vitamin E in sheep diet have positive effects on the growth performance and the quality of their meat products (Zhao et al, ).…”
Section: Application and Roles Of Vitamin E In Livestockmentioning
confidence: 99%
“…Among the different muscle tissues evaluated in our study, the highest oleic acid content was detected in supraspinatus, indicating that the meat quality of the supraspinatus can reduce cholesterol level in human blood. All SFA have an influence on cholesterol levels, expressed by the ratio of PUFA/SFA (Zhao et al, 2013).…”
Section: Discussionmentioning
confidence: 99%